Predicting mathematics students’ continuance intention toward learning mathematics / Muhammad Abdullahi …[et al.] - Abdullahi, Muhammad; Mohd Ayub, Ahmad Fauzi; Sulaiman, Tajularipin; Abdul Manaf, Umi Kalthom (Universiti Teknologi MARA, 2021)
The success of learning mathematics depends largely on students’ satisfaction in learning the subject. This, along with other factors such as perceived usefulness in learning mathematics, will eventually increase students’ intention to continue learning mathematics. This study integrated the Expectancy Confirmation Model (ECM) and perceived enjoyment, with the main purpose of developing a fitting structural model that investigates whether the ECM model can be extended and used in the context of mathematics students' learning continuance. The study used a correlational research design conducted on 12 tertiary colleges in the northwestern zone of Nigeria. Proportionate stratified random sampling technique was employed to select 366 Nigeria Certificate in Education (NCE) III mathematics combination students for this study out of a total population of 2761 NCE III mathematics students based on the Cochran formula. The findings indicate that the most significant factor affecting the college of education (COE) mathematics students' continuance intention is the belief of their perception of the usefulness of learning mathematics to their daily life activities. Satisfaction and perceived enjoyment in learning mathematics also positively influence students' intention to continue studying mathematics. The current research adds to the theory by replacing the ECM's confirmation of expectation construct with the construct of perceived enjoyment and introducing new associations to describe mathematics students' continued intention to learn mathematics.